2009
DOI: 10.1080/13576500802344420
|View full text |Cite
|
Sign up to set email alerts
|

The right ear but not the left ear temperature is related to stress-induced cortisolaemia in the domestic cat (Felis catus)

Abstract: Transport in containers and an unfamiliar environment are potent stress-inducing factors in domestic cats. This stress can be evaluated using cortisol concentration in serum and through other related physiological responses, such as increased glycaemia and body temperature. There is evidence that in some animal species, while subjected to psychological stress, lower right tympanic temperature is associated with emotional activation. In this study we evaluated the relationship between tympanic temperature, rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…A strong directionality was found, especially in lambs, reflecting a dominance of one brain hemisphere over the other in decision-making processes. Previous studies have reported that the right hemisphere has a dominant role in processing responses to acute stress (Tomaz et al 2003;Mazzotti and Boere 2009). Handling and social isolation, both being common farm practices, are known to be a stressful event for gregarious animals such as sheep (Boissy et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A strong directionality was found, especially in lambs, reflecting a dominance of one brain hemisphere over the other in decision-making processes. Previous studies have reported that the right hemisphere has a dominant role in processing responses to acute stress (Tomaz et al 2003;Mazzotti and Boere 2009). Handling and social isolation, both being common farm practices, are known to be a stressful event for gregarious animals such as sheep (Boissy et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in sheep social isolation stress is reduced by familiar faces and leads to increased activity in the right hemisphere [51], and strongly lateralized mothers had higher stress response than weakly lateralized mothers following separation from their young [52]. Further, stress induced temperature elevation in the right ear, corresponding to the right hemisphere, has been reported in marmosets [53] and cats [54]. Chronic stress causes neural damage in the right hemisphere in rats [55], and in humans suffering of major depressive disorders there is also a right hemisphere balance [56].…”
Section: Lateralization and Behaviourmentioning
confidence: 96%
“…in the form of differences in temperature of the tympanic membrane [26][27][28][29][30]. Such differences have been found to be associated with stress in several species (humans [32]; macaques [32]; cats [1]). Whether or not these differences are also reflected in a lateralized temperature differences at the level of the ear pinnae has not been investigated to date.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Stressors and negative emotional arousal are associated with physiological changes and alterations of blood flow patterns, which manifest as changes in body surface temperature ( [1]; reviewed in [2]). Infrared thermography represents a non-invasive way of measuring such changes, e.g.…”
Section: Introductionmentioning
confidence: 99%